Hicret’in 15. yüzyılında islâm sanatları sergisi : hat sanatı-yazma eserler ve fermanlar sergisi = On the occasion of the fifteenth centennial of hegira islamic arts exhibition : calligraphy, manuscripts and imperial edicts exhibition : İstanbul-Turkey. ([Ankara])
yak. 50 s.